WEARABLE ANTENNA DUAL BAND WITH ELECTROMAGNETIC BAND GAP (EBG) STRUCTURE FOR HEALTH APPLICATIONS - Haniifah Arif Ash-Shiddiq; Harfan Hian Ryanu; Levy Olivia Nur (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
Telemedicine can solve several issues in the healthcare system. The wearable antenna works with the Industrial, Scientific, and Medical (ISM) band for wireless body area network (WBAN) communications. Wearable antennas are lightweight, easy to make, and so on. This antenna application's bandwidth is limited by the thin substrate. This research will create a wearable planar monopole antenna with a circular patch that can operate at 2,4 and 5,8 GHz. Antenna without the UC-EBG structure and antenna with the UC-EBG structure were tested. The simulation results without UC-EBG show that the return loss is -14.629 dB and -28,639 dB, the VSWR is 1,456 and 1,077, the bandwidth is 4988 MHz, and the gain is 2,517 dBi and 4,270 dBi. The simulation results with the addition of UC-EBG show that the return loss is -13,835 dB and -17,46 dB, the VSWR is 1,511 and 1,309, the bandwidth is 1480 MHz and 2320 MHz, and the gain is 2,869 dBi and 5,208 dBi. The measurement results with UC-EBG show that the return loss is -13,134 dB and -18,421 dB, the VSWR is 1,566 and 1,273, the bandwidth is 1080 MHz and 960 MHz, and the gain is 2,198 dBi and 4,98 dBi.